Vínculo mãe-bebê: os encontros possíveis em uma UTI neonatal - Medeiros, Julliana de Paula (2010)
This study has as the purpose of understanding the maternal role in the hospitalization of preterm infants in a Neonatal Intensive Care Unit (NICU). The research was conducted at Hospital das Clínicas, Universidade Federal do Triângulo Mineiro in the period between March and June of 2009. Were interviewed five mothers, married, aged between 28 and 34 years. The approach used in this study is the psychoanalysis and is based on the transference phenomenon. The research took place in a dialogical perspective and the intersubjectivity has constituted a fundamental element of this psychoanalytic investigation. The NICU can be thought of as a symbolic space to the reframing of the traumatic experience of premature birth, the extent to which you can shift between motherly and fatherly functions of babies who are hospitalized there. The construction of the maternal function depends on the relation between this mother with her own childhood, how the baby was anticipated throughout gestation and the ability to invest in her desire for her son and beyond him. The motherly care is given from a series of assignments mother to her baby, by immersing the baby in a word universe that fall into one family line and that recognizes him as a desiring being. This con only occur if the mother is narcissistically able to reinvest in their real child, living the elaboration of mourning of the imaginary son, creating a psychological space between mother and baby, which will only happens if the mother has internalized the third. Among the factors and micro factors that contribute to a good mother-infant attachment we can highlight the acceptance of the neonatal health care team and the active participation in the care of the baby. On the other hand, as barriers, we have the lack of contact at birth, the passivity of the baby receiving the maternal care and the difficulty in maintaining the confinement period due to shifts hospital-home-hospital. Yet, as a inner psychic point of view a limitation for the binding, we need to deal with the possibility of losing the baby and the difficulty of narcissistic maternal investment, which can become unbearable in a situation where the premature baby presenting a visible bad formation.